The value of the use of renal function indices in distinguishing prerenal failure from established acute oliguric renal failure - Gunathilake, N.; De Mel, T.; De Mel, W.C.P.; Sheriff, M.H.R.; Dharmadasa, K. (My University, 1987)
:In a search for simple and reliable measurements to evaluate the common clinical dilemma of acute oliguric renal failure, 35 patients admitted to the University Medical Unit, Colombo, were prospectively studied. A table of indices formulated from blood and urinary; urea creatinine and sodium were used, based on similar studies done previously-i.e. a) Anderson et. al, New England Journal of Medicine 1977. b) Sporn, Lancestremere and Papper, New England Journal of Medicine 1962. c) Jones and weil, The American Journal of Medicine, 1971. d) Handa and Morin, Canad Med Assn J, 1967. These values were used to distinguish prerenal from established acute renal failure, and the clinical were compared with the biochemical findings. The objective of this study was to help diagnose early, potentially reversible conditions to prevent permanent structural damage to the kidneys. Except in three patients the indices compared well with the clinical findings. The two most useful values in decision making were, the fractional Excresion of Sodium (FEna) and the Renal Failure Index (RFI). We concluded that these simple tests in the absence of osmometry were very useful in delineating the pathogenesis of this common medical emergency.